2012
DOI: 10.1111/j.1095-8312.2011.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a complex phylogeographic structure in the common dormouse, Muscardinus avellanarius (Rodentia: Gliridae)

Abstract: This is the first mitochondrial phylogeography of the common dormouse, Muscardinus avellanarius (Linnaeus, 1758), a hibernating rodent strictly protected in Europe (Habitat Directive, annex IV; Bern Convention, annex III). The 84 individuals of M. avellanarius, sampled throughout the distributional range of the species, have been sequenced at the mitochondrial DNA gene (cytochrome b, 704 base pairs). The results revealed two highly divergent lineages, with an ancient separation around 7.7 Mya and a genetic div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
(94 reference statements)
1
16
0
Order By: Relevance
“…Samples were stored in sterile tubes at −20 • C. A total of 125 samples were collected from 25 populations around the UK (Table 1, Figure 1) and stored under licenses from Natural England and the UK National Trust. This sample size is commensurate with current standards for biogeographical genetic studies with the goal of estimating long-term divergence of lineages (see Gillespie, 2004;Mouton Figure 2A) and corresponding GenBank accession numbers for each gene. Reintroduction locations are indicated (*).…”
Section: Sampling Collectionmentioning
confidence: 74%
See 2 more Smart Citations
“…Samples were stored in sterile tubes at −20 • C. A total of 125 samples were collected from 25 populations around the UK (Table 1, Figure 1) and stored under licenses from Natural England and the UK National Trust. This sample size is commensurate with current standards for biogeographical genetic studies with the goal of estimating long-term divergence of lineages (see Gillespie, 2004;Mouton Figure 2A) and corresponding GenBank accession numbers for each gene. Reintroduction locations are indicated (*).…”
Section: Sampling Collectionmentioning
confidence: 74%
“…Three of our study sites were from reintroduced populations within the UK ( Table 1) as part of the dormouse reintroduction programme, to enable us to quantify genetic differentiation, if any, between these and natural populations. We analyzed UK data we produced along with previously published sequences available on GenBank from continental Europe (Mouton et al, 2012) and outgroup taxa.…”
Section: Sampling Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore referred our research in terms of habitat preference, because we aimed to determine the habitat features on which the settlement of our focal species (the edible dormouse, Glis glis) depends in a Mediterranean forest, and whether habitat requirements are the same between different age cohorts of individuals. The phylogeography of glirids (Hürner et al 2010, Lo Brutto et al 2011, Mouton et al 2012, Perez et al 2013) has been recently analysed in the Palaearctic by mitochondrial DNA analyses. Results on edible dormouse (Hürner et al 2010) have revealed two different lineages, namely the European and Italian lineage.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore referred our research in terms of habitat preference, because we aimed to determine the habitat features on which the settlement of our focal species (the edible dormouse, Glis glis) depends in a Mediterranean forest, and whether habitat requirements are the same between different age cohorts of individuals. The phylogeography of glirids (Hürner et al 2010, Lo Brutto et al 2011, Mouton et al 2012, Perez et al 2013 (Berg & Berg 1998, Lurz et al 2000, Wolton 2009) and southern Palaearctic (Cagnin et al 2000, Bertolino & Di Montezemolo 2007. Very few information about the ecology of G. g. italicus in peninsular Italy (Franco 1990, Capizzi et al 2003 and Sicily (Milazzo et al 2003) is available, and modelling on edible dormice habitat preferences in Mediterranean forests is totally lacking.…”
mentioning
confidence: 99%